2000
DOI: 10.3233/nre-2000-14306
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a balance and strength training program on equilibrium in Parkinsonism: A preliminary study

Abstract: The purpose of this study was to determine if a balance and strength training program could improve equilibrium and strength in persons with stage I-III Parkinsonism. Subjects were pre-tested on strength and balance (EquiTest) and randomized into either a treatment or a control group. The treatment subjects participated in 10 weeks of lower limb strength training and balance exercises designed to challenge a stable posture and increase limits of stability. Both groups were then posttested on balance, knee flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 33 publications
8
84
0
6
Order By: Relevance
“…Muscle strength was reported in four studies. 29,33,35,36 A significant improvement in leg muscle strength was reported by Hirsch et al 35 and Toole et al 33 Palmer et al 29 did not report between group differences although did report some improvements in grip strength in both the karate and stretching groups.…”
Section: Strengthmentioning
confidence: 85%
See 4 more Smart Citations
“…Muscle strength was reported in four studies. 29,33,35,36 A significant improvement in leg muscle strength was reported by Hirsch et al 35 and Toole et al 33 Palmer et al 29 did not report between group differences although did report some improvements in grip strength in both the karate and stretching groups.…”
Section: Strengthmentioning
confidence: 85%
“…Only two studies 38,41 reported power and sample size calculations. While two studies did not clearly report participant selection criteria, 33,36 the criteria reported in the other studies were varied, although all included a diagnosis of PD and being medically stable. Similarly, participant exclusion criteria also varied between the studies.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 3 more Smart Citations